2014
DOI: 10.3389/fpls.2014.00207
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing crop resilience to combined abiotic and biotic stress through the dissection of physiological and molecular crosstalk

Abstract: Plants growing in their natural habitats are often challenged simultaneously by multiple stress factors, both abiotic and biotic. Research has so far been limited to responses to individual stresses, and understanding of adaptation to combinatorial stress is limited, but indicative of non-additive interactions. Omics data analysis and functional characterization of individual genes has revealed a convergence of signaling pathways for abiotic and biotic stress adaptation. Taking into account that most data orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
243
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(251 citation statements)
references
References 253 publications
6
243
1
1
Order By: Relevance
“…Preliminary studies 21 performed by our research group already indicated the detrimental 22 effects of drought conditions in E. globulus plants (decreased water 23 potential, reduced gas exchange rates and stomatal conductance, 24 enhanced lipid peroxidation, among others) and correlated this 25 stress responses with changes in hormonal contents, namely 26 abscisic acid (ABA) and jasmonic acid (JA) (Correia et al, 2014a,b). 27 Understanding how planted forest trees tolerate low water 28 availability, studying new insights to anticipate its impacts and al pathways (Kissoudis et al, 2014) lead to changes in the biological 48 responses for the maintenance of plant stress tolerance (Wang and (Pastor et al, 1999). 61 The exogenous application of SA has been considered a short-62 term solution to improve the adverse effects of water deficit on 63 plants (Singh and Usha, 2003), however the precise mode of SA 64 action remains unclear (Hayat et al, 2010), in particular for trees.…”
mentioning
confidence: 99%
“…Preliminary studies 21 performed by our research group already indicated the detrimental 22 effects of drought conditions in E. globulus plants (decreased water 23 potential, reduced gas exchange rates and stomatal conductance, 24 enhanced lipid peroxidation, among others) and correlated this 25 stress responses with changes in hormonal contents, namely 26 abscisic acid (ABA) and jasmonic acid (JA) (Correia et al, 2014a,b). 27 Understanding how planted forest trees tolerate low water 28 availability, studying new insights to anticipate its impacts and al pathways (Kissoudis et al, 2014) lead to changes in the biological 48 responses for the maintenance of plant stress tolerance (Wang and (Pastor et al, 1999). 61 The exogenous application of SA has been considered a short-62 term solution to improve the adverse effects of water deficit on 63 plants (Singh and Usha, 2003), however the precise mode of SA 64 action remains unclear (Hayat et al, 2010), in particular for trees.…”
mentioning
confidence: 99%
“…Genome editing technologies have wide practical applications for solving one of the most important tasks of modern biotechnology-the creation of new varieties of crops, which are high-yielding and resistant to abiotic and biotic stresses and also have high nutritional value (Table 2) [31,63,[75][76][77][78][79][80]. To this end, genome editing system has been used in plant breeding (1) to insert point mutations similar to natural SNPs [26,27], (2) to make small modifications to gene function [13], (3) for integration of foreign genes, (4) for gene pyramiding and knockout, and (5) for the repression or activation of gene expression, as well as (6) epigenetic editing [6].…”
Section: Application Of Genome Editing Systems Inmentioning
confidence: 99%
“…Interactive effects of BRs and auxin involved physiological process such as hypocotyl elongation or root development. However, still, BR interaction with auxin in regulating stress responses has remained indefinable [67]. In Arabidopsis, the BR level required for development is interceded by BRAVIS RADIX (BRX) which is provoked by auxin showing that BRX demonstrations at the nexus of an input circle in Arabidopsis [68].…”
Section: Brs and Auxinsmentioning
confidence: 99%